Problem ubóstwa w Unii Europejskiej - Babiak, Jerzy (Przegląd Politologiczny, 2018)
The issues of poverty, famine and malnutrition mainly concern underdeveloped regions. Yet in recent years the proportion of the population threatened with poverty and social exclusion has been growing not only in these regions but also in developed areas, including the EU. The issue of poverty is additionally related to demography. In this context, the aging population of West European countries is worrisome, as the elderly are one of the groups particularly threatened by poverty, and their number continues to grow. Appreciating the gravity of this issue, the European Commission considers the fight against poverty to be one of the basic five directions established in the Europe 2020 strategic document.